Understanding what matters most to patients in acute care in seven countries, using the flash mob study design - Eva S. van den Ende; Bo Schouten; Marjolein N. T. Kremers; Tim Cooksley; Chris P. Subbe; Immo Weichert; Louise S. van Galen; Harm R. Haak; John Kellett; Jelmer Alsma; Victoria Siegrist; Mark Holland; et al. (BMC, 2021)
Abstract Background Truly patient-centred care needs to be aligned with what patients consider important, and is highly desirable in the first 24 h of an acute admission, as many decisions are made during this period. However, there is limited knowledge on what matters most to patients in this phase of their hospital stay. The objective of this study was to identify what mattered most to patients in acute care and to assess the patient perspective as to whether their treating doctors were aware of this. Methods This was a large-scale, qualitative, flash mob study, conducted simultaneously in sixty-six hospitals in seven countries, starting November 14th 2018, ending 50 h later. One thousand eight hundred fifty adults in the first 24 h of an acute medical admission were interviewed on what mattered most to them, why this mattered and whether they felt the treating doctor was aware of this. Results The most reported answers to "what matters most (and why)?" were 'getting better or being in good health' (why: to be with family/friends or pick-up life again), 'getting home' (why: more comfortable at home or to take care of someone) and 'having a diagnosis' (why: to feel less anxious or insecure). Of all patients, 51.9% felt the treating doctor did not know what mattered most to them. Conclusions The priorities for acutely admitted patients were ostensibly disease- and care-oriented and thus in line with the hospitals' own priorities. However, answers to why these were important were diverse, more personal, and often related to psychological well-being and relations. A large group of patients felt their treating doctor did not know what mattered most to them. Explicitly asking patients what is important and why, could help healthcare professionals to get to know the person behind the patient, which is essential in delivering patient-centred care. Trial registration NTR (Netherlands Trial Register) NTR7538 .